SHORT-FORM CONTENT, BRAIN ROT, AND BED ROT: A LITERATURE REVIEW OF THE IMPACT ON UNIVERSITY STUDENTS - Aysi, Alya Muhkbita Tasya Nur; Firdaus, Amanda Rahma; Pangestu, Surya Marcello; Utomo, Hanggara Budi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the cognitive and behavioral impacts of excessive short-form content consumption among university students, focusing on the phenomena of